HEMOGLOBIN LEVELS IN PREGNANT WOMEN LIVING IN COASTAL AND PLATEAU AREAS, KENDARI, INDONESIA - Rosanty, Anita; Yunus, Reni (YCAB Publisher & IAKMI SULTRA, 2017)
Background: Insufficient hemoglobin levels are one of the most vulnerable health problems during pregnancy. Hemoglobin levels less than 11 g/dL indicate anemia in pregnant women. However, it is assumed that there is a difference of hemoglobin levels between pregnant women in coastal and plateau areas. Objective: To compare the hemoglobin levels in pregnant women who live in the coastal and plateau areas in the working area of the Community Health Center of Mata, Kendari. Methods: This was an observational analytic research with cross sectional approach, conducted in May-June 2014. There were 38 pregnant women using quota sampling, divided into 19 respondents in coastal areas and 19 respondents in plateau areas. Blood sampling was performed in each respondent, and categorized into mild, moderate, and severe anemia. Data were analyzed using chi-square test. Results: The proportion of pregnant women with anemia in the working area of the Community Health Center of Mata was 94.74%. Chi-square test showed p-value 0.307 (>0.05). Conclusion: There was no significant difference in hemoglobin levels in pregnant women in coastal and plateau areas in the working area of the Community Health Center of Kendari district.